Your Co-author Received 150 Citations: Pride, but Not Envy, Mediates the Effect of System-Generated Achievement Messages on Motivation - Utz, Sonja; Muscanell, Nicole L. (Frontiers in Psychology, 2018)
ResearchGate, a social network site for academics, prominently displays the achievements of people one follows (“With 150 new reads, X was the most read author from their institute”). The goal of this paper was to examine the emotional and motivational effects of these system-generated messages, thereby extending prior research on envy-evoking status updates on Facebook to a professional context. We also extend the research on social comparisons and more broadly, on emotional responses elicited by social media. Specifically, social media research has largely focused on examining emotional reactions to content that is both generated by and is about others. In this research we directly examine updates generated by the system (ResearchGate) while also directly comparing reactions to updates about others’ achievements with reactions to updates that are about the self—i.e., one’s personal achievements which are also displayed on ResearchGate (“With 150 new reads, you were the most read author from your institute”). Particular attention was paid to the mediating role of envy and pride. The results of our quasi-experimental field study (n = 419) showed that the achievements of others elicited envy, whereas personal achievements elicited pride. People exposed to their personal achievements (vs. the achievement of others) showed a higher motivation to work harder. This effect was mediated by pride, but not envy. The theoretical and practical implications of these findings are discussed.